PLANTİNGA, BİLGİ VE DOĞRU İŞLEVSELCİLİK - Mehmet Sait Reçber (Felsefe Dünyası)
This paper provides a descriptive as well as a critical survey of Plantinga's recent epistemological project of "Proper Functionalism". After giving somewhat a detailed account of proper functionalism, it argues that the basic trouble with this view consists in its functionalist character. It is thus concluded that although Plantinga's proper functionalist view may provide a powerful explanation for background conditions of knowledge, it does not satisfactorily shed light on the nature of knowledge.